Pengaruh E-Filing, Sanksi, Kesadaran, Dan Sosialisasi Terhadap Kepatuhan Wajib Pajak Badan Pada KPP Pratama Gianyar - I Wayan Mertayasa; Ni Nengah Seri Ekayani; L.G.P Sri Eka Jayanti (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2021)
E-Filling, Tax Sanctions, Taxpayer Awareness, and Taxation Socialization on Corporate Taxpayer Compliance at Gianyar Tax Office. All corporate taxpayers registered at the Gianyar Primary Tax Office are 9,030 taxpayers with a sample size of 99 people based on the slovin formula. Sampling in this study was carried out using probability sampling with the incidental sampling technique. Data were analyzed using multiple linear regression analysis through the SPSS program. The results showed that E-Filling has a positive effect on Corporate Taxpayer Compliance at Gianyar Taxpayer Offices, Tax Sanctions have a positive effect on Corporate Taxpayer Compliance at Gianyar Taxpayer Offices, Taxpayer Awareness has a positive effect on Corporate Taxpayer Compliance at KPP Pratama Gianyar, Tax Socialization positive effect on Corporate Taxpayer Compliance at KPP Pratama Gianyar.